DETERMINING THE BEST INTERESTS OF THE CHILD IN CUSTODY BATTLES: SHOULD A CHILD’S VOICE BE CONSIDERED? - Frans Mashilo Mahlobogwane (Obiter, 2021)
South African courts and other Commonwealth Courts have long emphasized the notion that “best interests” of a child plays a significant role in custody decisions. When the court decides any question with respect to a child’s upbringing, it is under the duty to have regard to the ascertainable wishes and feelings of the child concerned. The weight to be given to the wishes and feelings has to be ascertained according to the child’s age or understanding. However, courts still face a complex task when having to determine the best interests of a child, for there is no easy way of establishing what these rights are. Most of the children who find themselves at thecentre of custody battles suffer the long-term and short-term stresses of divided loyalty. This paper will look at the following challenging questions: whether children are entitled to be consulted in major decisions affecting their custody, are children given any means of making their views known to the court, to what extent should a child’s view be considered, should those views be the only decisive factor.